Editorial: PINS @ 30 - Hayes, Grahame (PINS-Psychology in Society, 2025)
During 2013 we made mention that PINS (Psychology in society) had been going for 30 years, and that we wanted to mark this achievement in some way. The intention was to acknowledge and celebrate this 30 year publishing history, and at the same time use it as an occasion for some critical reflection of the journal’s past, present, and most importantly, its future. Through word-of-mouth amongst the editors we asked a range of people to write short critical and reflective pieces on PINS at 30. The interesting and thought-provoking collection assembled here is what we received from editors, colleagues, and other fellow travellers. Some others had intended to send us brief articles but time constraints and other work commitments conspired against them delivering on their “good intentions”. At the risk of over-indulging our narcissistic and celebratory impulses, PINS is prepared to take further commentary on its 30 year publishing history, and especially in the form of responses to the contributions published in this issue – PINS 46, that is, PINS @ 30.